Ile wart jest filolog? Wyobrażenia studentów a rzeczywistość rynku pracy - Grabowska, Monika Ewa; Smuk, Maciej; Sowa, Magdalena (Neofilolog, 2025)
This paper reflects on the metaphorical and economic value of philology graduates on the labour market. The starting point is an analysis of students’ social representations of the value of the language courses they are currently studying, and career prospects they perceive. In the second section, we present these perceptions of future careers and/or career plans, focusing on the areas of employment found most popular. In the third part the economic situation of graduates of various language majors in Poland is presented. The three-stage analysis allows comparison of students’ inherently subjective perceptions and objectively defined indicators of career success.